Pulmonary edema during the Boston Marathon. (2019) - Aoun, Joe; Dgayli, Khabib; Abou Zeid, Cynthia; Wong, Gordon; LaCamera, Peter
Abstract: The Boston Marathon is the most popular marathon in the New England region and attracts some of the most qualified athletes participating from the United States and abroad. The race occurs in April, a month in the northeast characterized by unpredictable weather. While there are a number of well described weather-related medical complications that occur during exercise, less is known about noncardiogenic pulmonary edema (NCPE) in marathon runners, a condition that most physician are unfamiliar with. This phenomenon has been described in the literature as a complication of severe hyponatremia and cerebral edema. Here, we describe the case of a healthy athlete who took part in the Boston Marathon in 2018 and presented afterwards with hypothermia and NCPE. We also review the normal cardiopulmonary physiology along with the physiological changes and external factors impacting the respiratory system during exercise. The combination of significant physical exertion, cold and rainy weather and subsequent hypothermia, perhaps along with other less understood factors may have increased the permeability of his lungs and caused NCPE.